Review of biogeographical ancestry markers and their application to forensic investigation (2017)
Purpose: The markers that determine biogeographical ancestry are booming, especially in the forensic field. These markers allow to analyze the dna of an individual and determine their biogeographical origin. These analyses are carried out frequently through SNP (Single Nucleotide Polymorphisms), but more recently through InDels as well. Because of this boom, the purpose of the review is to gather information about the markers currently being used, their different performance and their problems, as well as possible solutions. Period covered, origin and types of publications: The period covered for the analysis is 2006-2016, compiling articles from PubMed and Web of Science, with no preference as to origin.Point of view: Although they have been used for different populations and with different markers, they show similar results. Articles range from the types of markers selected for analysis, such as autosomal or lineage markers, to comparisons among markers in the same category, such as SNPS and InDels among autosomal ones. They have been thus selected to obtain a comparative view of the most effective for the detection of biogeographical ancestry. Conclusions: The most effective markers are autosomal AIM-SNP, in terms of differentiation among population groups, and supplementary AIM-InDels, in cases of population mixing.